A mild stressor induces short-term anxiety and long-term phenotypic changes in trauma-related behavior in female rats - Shanazz, Khadijah; Nalloor, Rebecca; Vazdarjanova, Almira (Frontiers in Behavioral Neuroscience, 2023)
Anxiety and anxiety-influenced disorders are sexually dimorphic with women being disproportionately affected compared to men. Given the increased prevalence in women and the documented differences in anxiety and trauma behavior between male and female rats this paper sought to examine the link between stress, anxiety, and fear learning and extinction in female Sprague-Dawley rats. We tested the hypothesis that a mild stressor will induce short-and long-term increases in anxiety and produce long term effects on subsequent fear learning and extinction behavior. We induced anxiety with a short exposure to a ball of cat hair (mild stressor) that elicits innate fear but does not cause fear conditioning. The control group was exposed to fake cat hair. We found that cat hair exposure induces changes in anxiety-like behavior in the short-term that appeared resolved 4 days later. However, the cat-hair exposed rats had long-term (2 weeks) phenotypic changes expressed as altered exploratory behavior in an emotionally neutral novel place. Fear learning and extinction were not impaired. Yet, using avoidance extinction, we demonstrated that the phenotypic difference induced by the mild stressor could be documented and dissociated from learning and memory. These findings demonstrate that the history of stress, even mild stress, has subtle longterm effects on behavior even when short-term anxiety appears resolved.